IN SILICO STUDY OF ARYL EUGENOL DERIVATIVES AS ANTI-COLORECTAL CANCER BY INDUCING OF APOPTOSIS - Fadilah, Fadilah; Yanuar, Arry; Arsianti, Ade; Andrajati, Retnosari; Purwaningsih, Erni Hernawati (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Apoptosis is one method the body uses to get rid of unneeded or abnormal cells, but cancer cells have strategies to avoid apoptosis. Apoptosis inducers can get around these strategies to cause the death of cancer cells. Methods: We screened some derivatives aryl eugenol based on their interactions with Bcl-2 in many cancer tissues, using computer software applications (in silico method) to determine the best compounds. The docking experiment on Bcl-2 (Protein Data Bank ID 4LXD) was carried out by suitably positioning the energy-minimized ligand in the active site while carefully monitoring non-bonded interactions of the ligand enzyme. Results: The resulting ligand-receptor complex was docked using the Autodock Vina software. Docking results based free binding energy, EUGACl (21), EUASABr (17), EUGEABr (19), and EUASACL (17), has the lowest binding energy than navitoclax and binds significantly to BCL 2. In silico ADMET predictions revealed that except SA, ASA, and GEA, all other compounds had minimal toxic effects and had good absorption as well as solubility characteristics. Conclusion: These compounds of aryl eugenol (17, 19, and 21) may serve as a potential lead compound for developing new anticancer as apoptosis inducers.